2012
DOI: 10.1007/s10554-012-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-contrast MR imaging for detecting endoleak after abdominal endovascular aortic repair

Abstract: Our aim was to investigate the possibility of ruling out endoleak after endovascular aortic repair (EVAR) of abdominal aortic aneurysm (AAA) using non-contrast MRI. Twenty-three patients (20 males, aged 73 ± 8 years) with an EVAR-treated AAA underwent 1.5-T MRI using axial, coronal and sagittal oblique true-FISP sequences. Two blinded and independent readers with 4 (R1) and 2 (R2) years of experience evaluated these images considering an area of even less than 5 mm in diameter with a signal intensity higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…When TOF-MRA imaging is used alone in patients with a low estimated glomerular filtration rate (eGFR), its sensitivity for endoleak detection can be as low as 54% (44). However, when TOF is used in conjunction with gadolinium-enhanced MRA, it has 97% concordance with angiography for the detection of endoleaks (45).…”
Section: Mramentioning
confidence: 99%
“…When TOF-MRA imaging is used alone in patients with a low estimated glomerular filtration rate (eGFR), its sensitivity for endoleak detection can be as low as 54% (44). However, when TOF is used in conjunction with gadolinium-enhanced MRA, it has 97% concordance with angiography for the detection of endoleaks (45).…”
Section: Mramentioning
confidence: 99%
“…The age of any thrombus within the sac can be evaluated based on the inherent signal characteristics of the thrombus composition. A recent study has shown that non-contrast MRA has high sensitivity for endoleak detection with a high negative predictive value using steady state free precession sequences [38]. MRA has also been shown to be at least as sensitive as CTA in the overall detection of endoleaks and is thought to be more sensitive than CTA in detecting Type II endoleaks [39,40].…”
Section: Magnetic Resonance Angiographymentioning
confidence: 99%
“…Resta et al [22] first reported the potential of unenhanced MR imaging for detecting endoleaks in their retrospective study of 23 patients. They used a true fast imaging with steady-state precession (FISP) sequence, which is a similar pulse sequence to ordinary BTFE.…”
Section: Discussionmentioning
confidence: 99%